2021
DOI: 10.1186/s12979-021-00226-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical COVID-19 protection mechanism: hints from centenarians

Abstract: The risk of serious complications and the fatality rate due to COVID-19 pandemic have proven particularly higher in older persons, putting a further strain in healthcare system as we dramatically observed.COVID-19 is not exclusively gerophile (géro “old” and philia “love”) as young people can be infected, even if older people experience more severe symptoms and mortality due to their greater frailty. Indeed, frailty could complicate the course of COVID-19, much more than the number of years lived. As demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…As expected, this excess mortality was higher than those observed in the Sicilian population that was 6% (55,583 deaths compared to 52,405) Examining centenarians separately the excess mortality raised to 28% and, again, was higher in men than in women (33% vs. 27%). These data confirm that women are more resilient to the virus than men as suggested by anecdotal findings discussed below [21,22], but not by the study conducted in Lombardy [14].…”
Section: Did Centenarians Die Less Than Remaining Older People?supporting
confidence: 79%
“…As expected, this excess mortality was higher than those observed in the Sicilian population that was 6% (55,583 deaths compared to 52,405) Examining centenarians separately the excess mortality raised to 28% and, again, was higher in men than in women (33% vs. 27%). These data confirm that women are more resilient to the virus than men as suggested by anecdotal findings discussed below [21,22], but not by the study conducted in Lombardy [14].…”
Section: Did Centenarians Die Less Than Remaining Older People?supporting
confidence: 79%
“…Despite that, worldwide reports of unvaccinated centenarians and supercentenarians (105 years or older) recovered from Covid-19 with mild or moderate symptoms called our attention [25][26][27][28][29]. Understanding why some individuals overcome the disease despite aging, such as the nun Ms. Randon, the oldest person already reported to survive Covid-19 at age 116 [30] is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Belenguer-Varea et al found that compared to the general elderly population, centenarians exhibited less oxidative damage, particularly lower plasma lipid peroxidation biomarkers (30). Franca Rosa et al suggested that centenarians had an unusual colony of cytotoxic CD4+ T cells under the effect of a human leukocyte antigen (31). Arai et al found that maintenance of insulin sensitivity, low prevalence of diabetes, and dysregulation of adipokines were characteristics of centenarians (32).…”
Section: Discussionmentioning
confidence: 99%